Primary renal liposarcoma simulating angiomyolipoma - Ryan C. Rizk, MS; Mohammad Yasrab, MD; Linda C. Chu, MD; Edmund M. Weisberg, MS, MBE; Elliot K. Fishman, MD (Radiology Case Reports, 2024)
Liposarcomas are infrequent malignant tumors of mesenchymal origin most commonly seen in the extremities. Although infrequent, these can develop as primary lesions in the soft tissue of the kidney, making them difficult to diagnose through imaging modalities alone. Primary renal liposarcomas are associated with poor prognoses, increasing the importance of timely and accurate diagnosis. In extremely rare instances, the tumor can arise directly from the fat in the epicenter of the kidney, disguised as an angiomyolipoma. In this article, we report the case of a 54-year-old female who was diagnosed with a well-differentiated liposarcoma of the kidney and underwent radical nephrectomy. Our objective is to evaluate unique radiological imaging findings and correlate with histopathological analysis to optimize diagnosis